Acid and alkali-resistant fabric-based triboelectric nanogenerator for self-powered intelligent monitoring of protective clothing in highly corrosive environments. Issue 17 (14th April 2023) - Chen, Ting; Song, Wei-Zhi; Zhang, Meng; Sun, De-Jun; Zhang, Duo-Shi; Li, Chang-Long; Cui, Wen-Ying; Fan, Ting-Ting; Ramakrishna, Seeram; Long, Yun-Ze
Abstract : The corrosion of materials severely limits the application scenarios of triboelectric nanogenerators (TENGs), especially in laboratories, chemical plants and other fields where leakage of chemically corrosive solutions is common. Abstract : The corrosion of materials severely limits the application scenarios of triboelectric nanogenerators (TENGs), especially in laboratories, chemical plants and other fields where leakage of chemically corrosive solutions is common. Here, we demonstrate a chemical-resistant triboelectric nanogenerator (CR-TENG) based on polysulfonamide (PSA) and polytetrafluoroethylene (PTFE) non-woven fabrics. The CR-TENG can stably harvest biological motion energy and perform intelligent safety protection monitoring in a strong corrosive environment. After treatment with strong acid and alkali solution for 7 days, the fabric morphology, diameter, tensile properties and output of CR-TENG are not affected, showing high reliability. CR-TENG integrated into protective equipment can detect the working status of protective equipment in real time, monitor whether it is damaged, and provide protection for wearers working in high-risk situations. In addition, the nonwoven-based CR-TENG has better wearing comfort and is promising for self-powered sensing in harsh environments.